Lumbar discopathy resolved with microdiscectomy - case report - Litak, Jakub; Litak, Joanna; Grochowski, Cezary; Miziak, Paulina; Budny, Agnieszka (Journal of Education, Health and Sport, 2018)
Low back pain is a widespread medical problem, fortunately most episodes are self limiting and resolve within 6 weeks. Many patients may be treated initially with conservative methods. Persistent sciatic pain or developing neurological deficits corresponding with MR scans pathologies of intervertebral disc (herniation , sequestration) are crucial for surgical qualification. We present patient with acute sciatica caused by disc herniation resolved with lumbar microdiscectomy.